Angiographic findings in two cases of aneurysmal malformation of vein of Galen prior to spontaneous thrombosis: therapeutic implications. - Hurst, R W; Kagetsu, N J; Berenstein, A (American Journal of Neuroradiology, 1992)
Two cases of aneurysmal malformations of the vein of Galen with later spontaneous thrombosis are reported. Angiograms before thrombosis in both cases showed mural type aneurysmal malformations of the vein of Galen with slow arteriovenous shunts and associated stagnation of contrast in the venous sac secondary to severe outflow restriction. Based on these angiographic findings, the patients were managed conservatively and the arteriovenous malformations of the vein of Galen thrombosed with good clinical outcomes. Twenty cases of spontaneous thrombosis previously reported in the literature are reviewed.